2010
DOI: 10.1007/s11999-010-1360-2
|View full text |Cite
|
Sign up to set email alerts
|

Cruciate-retaining TKA Using a Third-generation System with a Four-pegged Tibial Component: A Minimum 10-year Followup Note

Abstract: Level IV, therapeutic study. See the Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 46 publications
1
12
0
2
Order By: Relevance
“…Historically, many authors have advocated that the preservation of the posterior cruciate ligament in total knee arthroplasty is advantageous in providing better knee stability, prevention of posterior subluxation of the tibia, sheer stress reduction, increased knee joint proprioception and increased knee flexion due to better femoral rollback [2,3,23,24]. However, several reports have demonstrated that the posterior cruciate ligament in osteoarthritic knees is already histologically abnormal at the time of primary surgery [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, many authors have advocated that the preservation of the posterior cruciate ligament in total knee arthroplasty is advantageous in providing better knee stability, prevention of posterior subluxation of the tibia, sheer stress reduction, increased knee joint proprioception and increased knee flexion due to better femoral rollback [2,3,23,24]. However, several reports have demonstrated that the posterior cruciate ligament in osteoarthritic knees is already histologically abnormal at the time of primary surgery [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Several implant-specific studies have demonstrated over 95% survivorship for both posterior cruciateretaining (CR) and posterior cruciate-substituting (CS) TKAs with over 10-year follow-up [1][2][3][4]. However, in Swedish knee registry data [5], approximately 20% of patients who underwent TKAs were not satisfied with the outcome or uncertain about its benefit.…”
mentioning
confidence: 99%
“…for the most part decreased early aseptic failure rates of the tibial or femoral components [19,28].…”
Section: Introductionmentioning
confidence: 99%
“…La survie à dix ans de recul retrouvée dans notre étude nationale multicentrique est donc comparable à celle de nombreuses séries monocentriques contemporaines rapportant les résultats d'implants comportant un polyéthylène fixe [8][9][10][11][12][13] ou mobile [14][15][16][17][18][19] meilleurs scores KSS au recul ont été obtenus avec les PTG PS à PM dans cette étude avec des scores comparables à ceux déjà publiés au sein d'études monocentriques récentes [18,19], cette différence entre prothèses à PF ou mobile n'étant pas toujours retrouvée dans les études comparatives [20]. La flexion active moyenne notée dans ces séries monocentriques de la littérature oscille entre 105 • et 110 • [8][9][10][11][12][13][14][15], ce qui est légèrement inférieur à la flexion active moyenne de 112 • retrouvée dans la présente série.…”
Section: Discussionunclassified